Pengaruh E-service Quality dan Poduct Quality terhadap Repurchase Intention - Mohammad Deriatna; Leni Evangalista (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
The purpose of this study is to examine the influence of E-service Quality and Product Quality on Repurchase Intention for XL prepaid users in Bandung. The method used in this research is a quantitative approach. The population consists of men and women aged 18 years and older who have used XL prepaid SIM cards in Bandung. A total of 100 samples were selected, and the data source used is primary data collected through online questionnaires. The data collection technique employed is purposive sampling, which falls under the category of non-probability sampling. The data analysis technique used is multiple regression analysis, conducted with the assistance of SPSS version 30. The results of this study indicate that E-service Quality and Product Quality have a partial influence on Repurchase Intention. Furthermore, E-service Quality and Product Quality also have a simultaneous effect on Repurchase Intention.